A characterization for $B$-singular integral operator and its commutators on generalized weighted $B$-Morrey spaces - Hasanov, J.J.; Ekincioglu, I.; Keskin, C. (Carpathian Mathematical Publications, 2023)
We study the maximal operator $M_{γ}$ and the singular integral operator $A_{γ}$, associated with the generalized shift operator. The generalized shift operators are associated with the Laplace-Bessel differential operator. Our analysis is based on two weighted inequalities for the maximal operator, singular integral operators, and their commutators, related to the Laplace-Bessel differential operator in generalized weighted $B$-Morrey spaces.